Daily Functioning and Quality of Life in Patients with Sjögren–Larsson Syndrome - Staps, Pippa; de Groot, Imelda J.M.; van Gerven, Marjo H.J.C.; Willemsen, Michèl A.A.P. (Neuropediatrics, 2019)
Aim Sjögren–Larsson syndrome (SLS) is an autosomal recessively inherited neurometabolic disease caused by an enzyme defect in lipid metabolism. Patients suffer from intellectual disability, bilateral spastic paresis, ichthyosis, visual impairment, and photophobia. Knowledge about the meaning of having SLS in daily life is lacking.Methods Sixteen parents or caregivers of patients with SLS were asked to fill out online questionnaires about daily functioning, quality of life, feeding and swallowing problems, skin treatment, female hormonal status, and greatest problems.Results Questionnaires were filled out by parents or caregivers of six children and 10 adult patients, age range 11 to 58 years. The median quality of life score was 73 (range: 26–100). Most often reported problems were itchy skin, reduced mobility, and dependency. Feeding and swallowing problems were reported in 75% of the patients. Mood problems were rarely mentioned.Discussion Despite the large disruptions of daily functioning, patients with SLS are according to their parents generally content with their quality of life and participation. There was a broad range in reported problems. We found it very useful to systematically ask parents about their children's feelings and needs, to better understand the meaning of living with a complex disorder like SLS.
Keywords: Sjögren–Larsson syndrome; quality of life; participation; feeding and swallowing problems